2017
DOI: 10.1088/1612-202x/aa6704
|View full text |Cite
|
Sign up to set email alerts
|

Linearly-polarized random distributed feedback Raman fiber laser with record power

Abstract: We demonstrate a linearly polarized random distributed feedback Raman fiber laser with record 86.3 W output power with a piece of 157 m long polarization maintaining (PM) fiber. The maximum optical efficiency of first-order-Stocks light at 1120 nm reaches ~74% while pumping at 1070 nm. The full width at half maximum (FWHM) at maximum output power is ~2 nm and the polarization extinction ratio (PER) is measured to be as high as 22 dB. To the best of our knowledge, this is the highest output power for linearly-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Many studies have been carried out to enhance the already promising inherent features of RDFB-FL, for instance, the optimization of the output power [104][105][106][107], relative intensity noise transfer [108,109]and thermal noise [110]. In addition, their spectral and statistical properties have been analyzed in [111][112][113] and a variety of configurations have been proposed implementing polarized pump or linearlypolarized outputs [114][115][116][117], mixing different fibers in the gain media [118], short cavities [119,120] and tunable [121], multi-wavelength [57,[122][123][124][125] or super-continuum output [126,127]. Finally, RDFB-FL schemes allow combining the traditionally employed Raman amplification with other amplification mechanisms such as Erbium.…”
Section: Active Remote Fos Networkmentioning
confidence: 99%
“…Many studies have been carried out to enhance the already promising inherent features of RDFB-FL, for instance, the optimization of the output power [104][105][106][107], relative intensity noise transfer [108,109]and thermal noise [110]. In addition, their spectral and statistical properties have been analyzed in [111][112][113] and a variety of configurations have been proposed implementing polarized pump or linearlypolarized outputs [114][115][116][117], mixing different fibers in the gain media [118], short cavities [119,120] and tunable [121], multi-wavelength [57,[122][123][124][125] or super-continuum output [126,127]. Finally, RDFB-FL schemes allow combining the traditionally employed Raman amplification with other amplification mechanisms such as Erbium.…”
Section: Active Remote Fos Networkmentioning
confidence: 99%
“…Zhou et al has constructed an allfiberized fiber amplifier using active T-DCF [14] , and 53 W single frequency output at 1064 nm wavelength with M 2 ∼ 1.28 beam quality was obtained. Zhang et al and Lou et al have individually reported their passive T-DCF based random fiber laser system [15,16] . Up to present, the maximum output power of fiber laser based on long tapered fiber is 750 W with a beam quality of M 2 ∼ 1.7 [9] .…”
Section: Introductionmentioning
confidence: 99%
“…and Lou et al. have individually reported their passive T-DCF based random fiber laser system [15, 16] . Up to present, the maximum output power of fiber laser based on long tapered fiber is 750 W with a beam quality of [9] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, RRFLs have found applications in many fields, such as fiber optical sensing, pumping mid infrared laser and spectroscopic monitoring [2][3][4]. In previous studies, RRFLs with narrow linewidth, polarized output, cascaded generation, power scaling and pulsed operation have been realized [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%